Regulating Gig Work and Labor Protections in the Age of Platforms - Junki Utsumi; Katsuro Mizusawa; Yousuke Tachibana; Ippei Ogata; Hiroyuki Tetsuya (International Journal of Humanities, Management and Social Science (IJ-HuMaSS), 2025)
Japan’s rapid digital transformation has given rise to an expanding platform-based labor force in major urban centers such as Tokyo and Osaka. This study investigates how regulatory frameworks in Japan are responding to the rise of platform labor, focusing on the legal ambiguity, social protection gaps, and labor rights associated with gig economy work. While digital platforms promote flexibility and convenience, they also raise concerns over worker precarity, income instability, and exclusion from formal social safety nets. Using a descriptive qualitative methodology, this research analyzes recent legislative developments, policy debates, and case studies from delivery app workers, freelance digital content creators, and ride-hailing drivers. Findings suggest that while Japan has introduced partial regulatory measures, the country lacks a comprehensive legal framework to address the status of gig workers. The study contributes to ongoing debates on labor rights in the digital age and proposes future pathways for balancing innovation with inclusive labor protection.